CLUBROOT INCIDENCE AND SEVERITY ESTIMATES, ACCORDING TO THE SOIL pH - ARAUJO, Marla Alessandra; SOUZA, Jorge Luiz Moretti; LIMA NETO, Vismar Costa; BRONDANI, Gilvano Ebling (Scientia Agraria, 2009)
This study aimed to evaluate propensity of the Curitiba Metropolitan Region (26 cities) to the clubroot of crucifers incidence, through soil pH values. The 14452 pH in CaCl2 analyses were held by the Laboratory of Chemistry and Soil Fertility (DSEA / SCA / UFPR) during the period of 1999 and 2007. To check the disease incidence and severity propensity, there were faced the tendency measures with pH bands preset by literature. Except for Adrianópolis (59.4%) and Dr. Ulysses (33.3%), the other districts studied presented high propensity for the disease in its highest severity degree (pH < 5,7), with probability values higher than 75%. The results emphasized the necessity of liming and other practices of disease control.